2012
DOI: 10.1016/j.devcel.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal-Ventral Gene Expression in the Drosophila Embryo Reflects the Dynamics and Precision of the Dorsal Nuclear Gradient

Abstract: SUMMARY Patterning of the dorsal-ventral axis in the early Drosophila embryo depends on the nuclear distribution of the Dorsal transcription factor. Using live two-photon light-sheet microscopy, we quantified the nuclear Dorsal gradient in space and time and found that its amplitude and basal levels display oscillations throughout early embryonic development. These dynamics raise questions regarding how cells can reproducibly establish patterns of gene expression from a rapidly varying signal. We therefore qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
226
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(239 citation statements)
references
References 42 publications
(75 reference statements)
11
226
1
1
Order By: Relevance
“…It has been previously shown that Dorsal, a maternal morphogen that is required for twist transcription, is active in a gradient along the ventral-lateral axis with highest nuclear levels in the most ventral cells (Kanodia et al, 2009;Reeves et al, 2012). twist expression levels have previously been described as being uniform across the central region of the ventral furrow with a gradient of twist at the edge of the furrow, where cells stretch (Leptin, 1991).…”
Section: An Upstream Regulator Of Contractility T48 Exists In a Gramentioning
confidence: 99%
“…It has been previously shown that Dorsal, a maternal morphogen that is required for twist transcription, is active in a gradient along the ventral-lateral axis with highest nuclear levels in the most ventral cells (Kanodia et al, 2009;Reeves et al, 2012). twist expression levels have previously been described as being uniform across the central region of the ventral furrow with a gradient of twist at the edge of the furrow, where cells stretch (Leptin, 1991).…”
Section: An Upstream Regulator Of Contractility T48 Exists In a Gramentioning
confidence: 99%
“…The nuclear concentration of Bicoid during the final five nuclear cycles remains mostly constant during each nuclear cycle, indicating that Bicoid itself activates transcription of AP genes at a constant rate through these nuclear cycles (Gregor et al 2007). In contrast, the protein product of the maternal gene dorsal, found in a DV gradient, increases in concentration within nuclei during each of the final five nuclear cycles (Reeves et al 2012). This increase in nuclear Dorsal concentration suggests that the DV network is activated differently at each nuclear cycle, both by Dorsal itself, and by a network of transcription factors that respond to different levels of Dorsal.…”
mentioning
confidence: 98%
“…In Drosophila melanogaster, the MZT takes place within the first 3 hr of development, during the late syncytial nuclear divisions and ending at the cellular blastoderm stage with gastrulation (Foe and Alberts 1983;Pritchard and Schubiger 1996;Tadros and Lipshitz 2009). Gene expression during the MZT is highly dynamic, with patterns of zygotic genes first being established and changing between and within nuclear cycles (Stathopoulos and Levine 2005;Reeves et al 2012). It is clear, therefore, that each syncytial nuclear cycle can be treated as a single, or even multiple developmental time points.…”
mentioning
confidence: 99%
“…In both Drosophila and Tribolium, Toll signalling leads to the formation of a ventral-to-dorsal nuclear gradient of the NF-κB transcription factor Dorsal. The NF-κB/Dorsal gradient is fairly stable in Drosophila and patterns the DV axis by activating or repressing target genes in a concentration-dependent manner (Hong et al, 2008;Ozdemir et al, 2014;Reeves and Stathopoulos, 2009;Reeves et al, 2012;Roth et al, 1989;Rushlow et al, 1989;Steward, 1989). Among the targets of NF-κB/Dorsal are transcription factors directly involved in cell fate specification such as twist (twi), as well as components of other signalling pathways which indirectly specify subregions along the DV axis.…”
Section: Introductionmentioning
confidence: 99%